Integrated Cobaloxime and Mesoporous Silica-Supported Ruthenium/Diamine Co-Catalysis for One-Pot Hydration/Reduction Enantioselective Sequential Reaction of Alkynes - Liu, Zeyang; Wang, Yongjie; Liu, Kaihong; Wang, Shanshan; Liao, Haocheng; Zhu, Yuanli; Hou, Baoming; Tan, Chunxia; Liu, Guohua (Frontiers in Chemistry, 2021)
This study developed a cost-efficient hydration/asymmetric transfer hydrogenation (ATH) process for the one-pot synthesis of valuable chiral alcohols from alkynes. During this process, the initial homogeneous cobaloxime-catalyzed hydration of alkynes was followed by heterogeneous Ru/diamine-catalyzed ATH transformation of the in-situ generated ketones, which provided varieties of chiral alcohols in good yields with up to 99% ee values. The immobilized Ru/diamine catalyst could be recycled at least three times before its deactivation in the sequential reaction system. This work shows a general method for developing one-pot asymmetric sequential catalysis towards sustainable organic synthesis.